The rare genus Therophilus Wesmael (Braconidae: Agathidinae) in Brazil with description of two new species - Iza-Campos, Giulia; Penteado-Dias, Angélica (Zootaxa, 2021)
Two new species of Therophilus Wesmael (Braconidae: Agathidinae) from Brazil are described: T. shimborii sp. n. and T. onodyi sp. n. Maps with the collection sites of both species are presented.